The safety and efficacy of Onivyde (irinotecan liposome injection) for the treatment of metastatic pancreatic cancer following gemcitabine-based therapy. Issue 7 (2nd July 2016) - Passero, Frank C.; Grapsa, Dimitra; Syrigos, Kostas N.; Saif, Muhammad Wasif
ABSTRACT: Introduction : Patients with advanced and metastatic pancreatic cancer refractory to gemcitabine based therapy have a dismal prognosis and limited therapeutic options. Recently, the FDA approved nanoliposomal irinotecan combined with fluorouracil/folinic acid for such patients based upon results of the NAPOLI-1 study which showed this regimen compared to fluorouracil/folinic acid significantly prolonged progression free survival (3.1 vs. 1.5 months) and overall survival (6.2 vs. 4.1 months). Areas covered : The pharmacokinetic and pharmacogenetic characteristics of this novel formulation of irinotecan, its safety profile, and use in a clinical context for patients with pancreatic cancer are reviewed. Expert commentary : Nanoliposomal irinotecan, in combination with 5-FU/folinic acid, represents an important step forward in improving second line treatment options in patients with progression of metastatic pancreatic cancer. Furthermore, the novel drug formulation offers pharmacokinetic advantages which serve as a basis for further clinical testing in a various pancreatic cancer settings and other malignancies.